Frontmatter (Front Cover, Editorial Team, Focus & Scope, Table of Contents) - Dian Bayu Firmansyah (Faculty of Humanities, Universitas Jenderal Soedirman, 2019)
Jurnal Ilmiah Lingua Idea, Vol 10, Issue 2, December 2019